Maternal Risk Factors of Placenta Praevia and Its Effects on Maternal and Fetal Outcome (Bangladesh Medical Journal, 2019)
Placenta praevia is one of the most serious obstetric emergencies, which continues to be an important contributor to perinatal mortality and is responsible for leading maternal and infant morbidity. Very few data on etiology of placenta praevia are available till now. This study aims to explore the maternal risk factors related to occurrence of placenta praevia and its effects on maternal and fetal outcome. This cross-sectional observational study was carried out among 3279 obstetrics patients admitted in labour ward in the Department of Obstetrics and Gynecology, Sher-e-Bangla Medical College Hospital from January to December 2006. Out of 3279 obstetrics patients 93 placenta praevia cases were identified purposively as study subjects. The patients of placenta praevia were selected either diagnosed clinically by painless antepartum haemorrhage or asymptomatic placenta praevia diagnosed by ultrasonography irrespective of age, gestational age, parity, booking status. Pregnant woman admitted with painful antepartum haemorrhage were excluded from the study. With the ethical approval from the Institutional Ethical Committee (IEC), patients were selected after taking their written consent. A structured questionnaire and a chick list were designed with considering all the variables of interest. Out of 93 respondents, 73.88% were associated with risk factors in addition to advanced maternal age and high parity. Among them 24.73%, 33.33% and 7.52% had history of previous caesarean section (CS), MR and abortion and both CS & abortion previously. Patients aged above 30 years were 47% and 35.48% were in their 5th gravid and more; whereas, 31.18% patients were asymptomatic, 68.82% patients presented with varying degree of vaginal bleeding, among them 12.08% were in shock. Active management at presentation was done on 76.34% patients and 23.66% were managed expectantly. CS was done o 82.79% patients and only 17.2% were delivered vaginally. Case fatality rate was 1.07% and about 22% perinatal death was recorded, majority belonged to low birth weight (